ABOUT TACTICS OF TREATMENT OF ACUTE PANCREATITIS COMPLICATED BY MECHANICAL JAUNDICE - G.N.Rayimov; X.M. Xodjiyev; Sh.B. Mansurxodjayev (Scholar Express Journals, 2023)
The aim of the study was to improve the results of treatment of patients with OP in the presence of jaundice syndrome by improving the method of differential diagnosis of the nature of concomitant jaundice
Keywords: acute pancreatitis; mechanical and parenchymal jaundice,; laparoscopic cholecystectomy; choledocholidiasis